A Chinese resource curse? The human rights effects of oil export dependence on China versus the United States. (November 2015) - Bader, Julia; Daxecker, Ursula
Critiques of China's 'oil diplomacy' center on its alleged disregard for transparency and human rights, yet such claims ignore that the problematic relationship between resource extraction and human rights precedes Chinese market entry. This article explores whether human rights implications are more serious for states exporting oil to China compared to another major oil importer, the United States. Contrary to the conventional wisdom, we argue that oil export dependence on the USA affects human rights more negatively than dependence on China because of differences related to the timing of market entry. The United States established stable relationships with oil supplier states decades ago, creating dependencies that are sufficiently long-term for the implications of the resource curse to take hold, and taking place before human rights became part of the US foreign policy agenda. In comparison, China's late entry into global oil markets in the early 1990s meant that market access often required the provision of generous loan packages, which may help counteract the detrimental effects of oil dependence. Our empirical analysis examines the impact of oil export dependence on China versus the USA on human rights in supplier states for the 1992–2010 period. Results show that oil producing states dependent on exports to the USA exhibit lower human rights performance than those exporting to China. We also demonstrate that lower human rights performance for US exporters stems from long-term trends rather than short-term fluctuations in oil export dependence.